2007
DOI: 10.1002/hep.21583
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive bead assay for antimitochondrial antibodies: Chipping away at AMA-negative primary biliary cirrhosis

Abstract: The antimitochondrial response in primary biliary cirrhosis (PBC) is the most highly directed and specific self-reacting antibody in human immunopathology. Originally, antimitochondrial antibodies (AMAs) were detected by indirect immunofluorescence (IIF) and found in approximately 90% of well-documented patients with PBC. The introduction of recombinant autoantigens and the use of immunoblotting have increased the sensitivity and specificity of AMAs, and they are now considered positive in approximately 95% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 32 publications
1
107
1
3
Order By: Relevance
“…In studies of AMA reactivity in large numbers of sera, we have demonstrated that when recombinant antigens are used for immunodiagnosis, they are strikingly specific for PBC; we have also shown that such specificity and sensitivity is dramatically increased with the use of ELISA and/or immunoblot assays compared with immunofluorescence. 21,24,25 In our initial analysis and our observations that AMAs were indeed found in ALF, we decided to replicate the data in a second site-hence the duplicate analysis at both UC Davis and Teikyo University (both sites had identical results). Recent work has suggested that posttranslational modification of the mitochondrial 2-OADC lipoyl moiety is a possible mechanism in the initiation of AMAs in PBC.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of AMA reactivity in large numbers of sera, we have demonstrated that when recombinant antigens are used for immunodiagnosis, they are strikingly specific for PBC; we have also shown that such specificity and sensitivity is dramatically increased with the use of ELISA and/or immunoblot assays compared with immunofluorescence. 21,24,25 In our initial analysis and our observations that AMAs were indeed found in ALF, we decided to replicate the data in a second site-hence the duplicate analysis at both UC Davis and Teikyo University (both sites had identical results). Recent work has suggested that posttranslational modification of the mitochondrial 2-OADC lipoyl moiety is a possible mechanism in the initiation of AMAs in PBC.…”
Section: Discussionmentioning
confidence: 99%
“…This preparation contains all three immunodominant mitochondrial antigenic epitopes, namely PDC-E2, BCOADC-E2 and OGDC-E2 [88] . Although assays based on MIT3 are reported to give positive results for PBC sera that test negative for AMA by conventional IFL techniques [89,90] , IFL testing for AMA should remain the screening procedure.…”
Section: Mitochondrial Antigensmentioning
confidence: 99%
“…They may be of diagnostic assistance, especially in those cases where it is difficult to interpret the IFL staining patterns due to concurrent autoantibody reactivities or in true AMAnegative PBC cases [ of ACA reactivity in the combined PBC/CREST disease. Assays to detect multiple reactivities (multiplex) and to provide a full autoimmune serological profile of relevance to PBC are being developed [89] . At present, a lack of guidelines for the detection of PBC-specific autoantibodies by scientific bodies responsible for the standardization of autoimmune serological tests is a significant handicap and perpetuates uncertainties on which are the clinically relevant tests (see below).…”
Section: Pbc-specific Nuclear Antigensmentioning
confidence: 99%
“…64,65 Autoantibodies Circulating AMAs are highly specific for PBC and are detected in nearly 100% of patients when tested for using techniques based on recombinant mitochondrial antigens (immunoblotting or enzymelinked immunosorbent assay). The high sensitivity and specificity of AMAs make them one of the most specific diagnostic tests of human immunopathology, 66 different from other autoimmune conditions, 67,68 including autoimmune hepatitis. 69 In most clinical settings for initial screening, AMAs are usually detected by indirect immunofluorescence using rodent liver, kidney and stomach sections as a substrate, leading in some cases to false positive or negative results.…”
Section: What Causes Liver Damage?mentioning
confidence: 99%